Contributing factors towards adherence to antiretroviral therapy among people living with HIV at a University Teaching Hospital in Nigeria - Eze, Rosemary Ada (2022)
Nigeria is ranked second in Sub-Saharan Africa, behind South Africa, and third globally, behind India, in terms of illness burden (HIV). In 2019, 1.9 million Nigerians were living with human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS), with a prevalence of 1.4 percent among adults. In 2017, only 33% of persons living with HIV were receiving treatment. Compliance to antiretroviral therapy (ART) is a complicated process influenced by a variety of factors, and various studies have sought to identify the hurdles and facilitators to ART adherence using socioecological model. The findings imply that HAART medication non-adherence is a complicated issue involving multiple levels of the system. The current study aimed to determine the contributing factors towards adherence to ART at Ahmadu Bello University Teaching Hospital Zaria Nigeria (ABUTH) using a social ecological framework, which consist of individual level, community level and interpersonal level. From June to September 2019, a cross-sectional study, utilising a systematic random sampling procedure. Respondents aged 18 to 64 living with HIV on ART at ABUTH, Zaria, Kaduna State, were invited to participate in the study; adults who were too sick owing to an illness or mental issue throughout the research period, such as infectious illnesses or Alzheimer`s disease, were not considered eligible. A 6-item scale from the US Household Food Security Survey Module was used to assess food insecurity The 10- item CES-D scale was used to assess respondents' depression symptoms, and the CASE Adherence test was utilised to examine adherence to ART. The functional social support questionnaire (FSSQ) developed by Duke and UNC was adapted to assess the respondents' social support network's strength. The respondents' perceptions of stigma were assessed using a questionnaire adapted from Wright's HIV stigma scale, Adult AIDS Clinical Trials Group questionnaire was modified to assess respondents' drug and alcohol consumption, as well as the side effects of antiretroviral medication. HIV Knowledge Questionnaire 18 was used to assess people living with HIV's HIV-related knowledge and beliefs about Medicines Questionnaire (BMQ) was adapted to access patients' beliefs and concerns regarding the necessity for prescription medication to control their illness. Data on socio-demographic and 24-hour dietary recalls were obtained through face-to-face interviews. Anthropometric measurements including weight, height were conducted. Pearson's chi-square or Fisher exact tests were used to explore the association between adherence to ART as a dependent variable and the independent variables. A multivariate regression analysis was undertaken to identify the contributing factors towards adherence to ART among people living with HIV on ART in ABUTH. Starting with simple logistic regression with p 0.25. Using an entry variable selection, multiple logistic regression with a 95% confidence interval was performed. The alpha 0.05 significance level was used. Results indicated that, among 385 respondents the prevalence of adherence to ART among adults on ART in ABUTH was 54% in which (67.5%) were female and (32.5%) were male. Most of the respondents were aged 49-64 years old (50.9%), about (44.9%) of the respondents attended tertiary level of education. Most of the respondents (76.1%) were depressed and more than half of respondents were moderate alcohol drinkers (51.4%). Majority of the respondents (81.3%) had poor knowledge towards HIV transmission and ART. Majority of the respondents (87.0%) displayed low food security. More than half of the respondents (52.5%) were within the normal BMI classification and (40.3%) were overweight. Most of the respondents (74.8%) displayed moderate diet diversity. Male and female respondent achieved 75% and 76% of energy intake of RDA respectively and 64% and 60% protein intake of RDA respectively. About 48.1% of the respondent experience side-effect from the medication. Most of the respondents (75.3%) were unsatisfied with the health-care service. More than half of the respondents (55.8%) had negative perceptions (beliefs) of personal need for the medication, while 42.3% of the respondents had more concerns about the potential negative effects of the medication. About 25.7% of the respondents could not disclose their status to anyone due to fear of rejection, and about 44.7% of the respondents face high stigma and discrimination from people and 42.1% of the respondents face poor social support from people. Significant association was found between age (ꭓ² =9.179, p <0.01), education (ꭓ²=8.458, p <0.01), occupation (ꭓ² =9.061, p <0.01), marital status (ꭓ² =7.293, p <0.05), BMI (ꭓ² =12.387, p <0.01), diet diversity (ꭓ² =10.255, p <0.01), food insecurity (ꭓ² =11.446, p <0.01), depression (ꭓ² =13.245 p <0.05), knowledge (ꭓ² =12.304, p <0.05), difficulties getting ART on time (ꭓ² =10.773, p <0.01), distance to clinic (ꭓ² = 10.477, p <0.01), respondents beliefs (ꭓ² =12.812, p <0.05), disclosure to family member (ꭓ² =10.431, p <0.05) stigma/discrimination (ꭓ² =11.692, p <0.05), social support (ꭓ² =34.797, p <0.01) and adherence to ART. Multiple logistic regression revealed that respondents who were self-employed increased the odds by two times (AOR = 2.646, 95% CI: 1.335, 5.241) and government employed increased the odds of non-adherence to ART by 2.8 times more than respondents who were unemployed (AOR = 2.842, 95% CI: 1.542,5.240). Respondents who were (divorced or widow) were two times more likely to become non-adherence to ART (AOR = 2.016, 95% CI: 1.111, 3.660). Respondents who were food insecure were 1.2 times more likely to be non-adherence to ART (AOR = 1.220, 95% CI: 1.642, 2.319). Respondents who had low dietary diversity were 1.7 times more likely to be nonadherence (AOR = 1.792, 95% CI: 1.023, 3.139) and respondents who had negative perceptions of personal need for the ART were 1.5 times more likely to be non-adherence to ART (AOR= 1.525, 95% CI: 1.958-2.427), respondents who had more concerns about the potential negative effects of the ART medication were 1.3 times likely to be nonadherence to ART (AOR= 1.362, 95% CI: 1.751-2.005). Respondents who had poor social support increased the odds by threefold of non-adherence to ART (AOR = 3.956, 95% CI: 2.424, 6.456). In conclusion, adherence to antiretroviral therapy (ART) remains a major challenge for people living with HIV/AIDS in Nigeria. Factors associated with adherence to ART identified in this study were occupation, marital status, food insecurity, dietary diversity, patient belief and social support. Health care personnel must be aware of these concerns and the belief of the respondents towards medicine. Workplace regulations must be in place to assist persons with chronic conditions such as HIV/AIDS in sticking to their treatment regimens. Improved food shortages can result to better compliance with treatment and care guidelines, intervention studies are needed to figure out how to reduce non-adherence. Family, friends and community must play a role in encouraging people living with HIV to adhere to antiretroviral medication. Patient-centered measures should be taken to establish appropriate adherence-enhancing interventions. Health care providers and HIV control programme implementers should emphasize on adverse drug reactions.